Melanchthon's contribution to the art of catechesis: A study of Catechesis puerilis. Issue 3 (October 2016) - Oseka, Matthew
The present paper explores Melanchthon's contribution to the art of catechesis as typified by his Catechismus puerilis and by his Catechesis puerilis . It also examines the origin of Protestant catechisms in light of instruments of theological instruction employed in the ancient and mediaeval church. Furthermore, theological highlights of both catechetical manuals authored by Melanchthon were presented as far as the Protestant concept of vocation was concerned.